The effects of urbanization on vegetation conditions in coastal zone of China - Huang, Baoying; Li, Zhijian; Dong, Chengcheng; Zhu, Zaichun; Zeng, Hui (Progress in physical geography, 2021)
Vegetation in urban settings is heavily altered by anthropogenic impacts. However, the impacts of urbanization on vegetation are not well understood. Here, we quantified the impacts of urbanization on vegetation in 48 Chinese coastal cities and explored their dynamic characteristics from 1990 to 2015. The indirect impacts of urbanization on vegetation at different spatial and temporal scales were also determined. Remote-sensing-based results indicated that vegetation conditions decreased significantly as the proportion of built-up land increased. However, the difference between the observed decline trend and the theoretical one means that urbanization in most coastal areas promoted vegetation growth. Except vegetation loss from land changes, there had been positive indirect effects of urbanization on vegetation conditions at several scales in coastal areas across the study period. These positive indirect impacts are attributed to the balances between vegetation restoration and management, the deterioration of plants’ living conditions, and urban microclimate. Due to Chinese environmental actions over 25 years, the number of cities with a positive indirect impact increased. Our study might enhance the systematic understanding of the response of vegetation to urbanization in China.